SINERGITAS DALAM PEMBINAAN DAN PENATAAN PEDAGANG KAKI LIMA (PKL) DI KOTA BANDUNG - Zaenal Abidin As (Jurnal Caraka Prabu, 2019)
The existence of street vendors (PKL) in several big cities in Indonesia has caused a polemic which is still hot in discussion, where this relationship with spatial planning patterns in an area is causing problems. The problem of street vendors is not a new problem that only exists in Indonesia, even in Latin America and the Middle East itself experiencing the same thing, and the problem of the places where they sell sales and licensing is also a problem. The handling pattern by prioritizing synergy between the government and other parties in the handling process can answer problems related to the existence of street vendors in an area. Bandung city as a metropolitan city "Paris van Java" which provides location centers and tourist centers in the city center. Of course, this cannot prevent the city of Bandung from being at street vendors. The synergy that exists between the government and street vendors in the city of Bandung has resulted in several innovations including Monday without street vendors, this idea is the concern of street vendors for the condition of the city of Bandung with their existence who are often accused of being the cause of several problems and breakthroughs of the Bandung City Government that previously were not conducted in other urban areas in Indonesia, namely the construction of the "Skywalk" in the Cihampelas area of ​​Bandung city. Where the skywalk is intended as a means of walking as well as serving to serve street vendors along the Cihampelas shopping route. Keywords: Synergy and street vendors.